Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/ijms222413544
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Koizumi and Longa Methods of Intraluminal Filament Middle Cerebral Artery Occlusion in Rats: Early Corticosterone and Inflammatory Response in the Hippocampus and Frontal Cortex

Abstract: Two classical surgical approaches for intraluminal filament middle cerebral artery occlusion (MCAO), the Longa et al. (LM) and Koizumi et al. methods (KM), are used as alternatives in preclinical studies to induce stroke in rodents. Comparisons of these MCAO models in mice showed critical differences between them along with similarities (Smith et al. 2015; Morris et al. 2016). In this study, a direct comparison of MCAO-KM and MCAO-LM in rats was performed. Three days after MCAO, infarct volume, mortality rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 52 publications
1
27
1
Order By: Relevance
“…It should be noted that the hippocampus and prefrontal cortex are central structures of the cortico–limbic network associated with both cognitive processes (e.g., learning and memory) and the control of emotions [ 46 ], whereas their dysconnectivity may underlie different brain diseases [ 47 ]. This may explain why both in our previous [ 15 ] and present study, we found similar trends to the increased corticosterone accumulation both in the hippocampus and FC of the MCAO-KM rats. Importantly, the accumulation of corticosterone and Il1β in the hippocampus and FC was not only in the injured but also in the contralateral hemisphere, which substantiates the hypothesis of potential distant damage.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…It should be noted that the hippocampus and prefrontal cortex are central structures of the cortico–limbic network associated with both cognitive processes (e.g., learning and memory) and the control of emotions [ 46 ], whereas their dysconnectivity may underlie different brain diseases [ 47 ]. This may explain why both in our previous [ 15 ] and present study, we found similar trends to the increased corticosterone accumulation both in the hippocampus and FC of the MCAO-KM rats. Importantly, the accumulation of corticosterone and Il1β in the hippocampus and FC was not only in the injured but also in the contralateral hemisphere, which substantiates the hypothesis of potential distant damage.…”
Section: Discussionsupporting
confidence: 91%
“…For rats showing a neurological deficit according to the 5-point scale, the survival rate within 48 h was 52% (12 of 23) for the MCAO-KM rats and 52% (11 of 21) for the MCAO-LM rats; the survival within 3 months was 35% (8 of 23) and 43% (9 of 21), respectively. The short-term survival did not differ significantly from the data reported previously for the MCAO-KM (57% within 72 h) and the MCAO-LM (63%) [ 15 ]. Similar to the reports of Smith et al [ 13 ] and Morris et al [ 14 ], in mice, the mortality did not differ in the MCAO-LM and MCAO-KM and was very high during the first 24 h after MCAO (e.g., the after 60 min occlusion survival rate was 38.5% within 24 h in the MCAO-KM mice).…”
Section: Resultscontrasting
confidence: 65%
See 3 more Smart Citations